Estudo de toxicologia clínica e genotoxicidade do fitoterápico tamaril® cápsula, em voluntários sadios - Vasconcellos, Marne Carvalho de (2004)
Tamaril® is a phytomedicine constituded of 5 medicinal plants well known for their laxative proprieties: Cassia fistula (soft extract), Cassia angustifolia (Senna), Coriandrum sativum L. e Glycyrrhiza glabra L. (Alcaçuz) and Tamarindus indicus L. (soft extract). Every medication to be launched on the market must succeed in a series of research steps, where clinical toxicology evaluation is an important one among them. Genotoxic assessment, which aims on the processes altering DNA integrity, is a relatively recent field in drug development and stands on the interface between toxicology and genetics. This study consisted on the evaluation of clinical safety and genotoxic potential of Tamaril® capsules in healthy volunteers. The clinical evaluation consisted of an open study with 25 healthy volunteers of both sexes (13 males and 12 females) who received a daily oral dose of two capsules Tamaril® for 28 consecutive days. The volunteers were selected for the study if considered in good health after criterious clinical, physical and laboratorial evaluations. At the end of the 28 study days, blood samples (5 mL) were collected from each volunteer for the genotoxic assessment of Tamaril® on peripheral lymphocytes through the comet assay. The mean age of the volunteers was of 30.1± 6.9 years and the body mass index was of 24.21±3.00 Kg/cm2 on the pre-study evaluation and 24.26±3.05 Kg/cm2 on the post-study. Hematological, hepatic, renal and metabolic functions, as well as sodium and potassium did not show signs of abnormality in any volunteer throughout the weeks of the study. Soften faces, abdominal pain and flatulence were the adverse events regularly observed. Through the comet assay, score 1 DNA damage was most frequently registered on peripheral lymphocytes of volunteers treated with Tamaril® (p<0.05). Clinical and genotoxic evaluation of healthy volunteers receiving Tamaril® for 28 uninterrupted days did not show signs of toxicity related to the treatment.